Pengaruh Motivasi Terhadap Peningkatan Profesionalisme Guru - Adam, Adiyana (Sekolah Tinggi Agama Islam Babussalam Sula, 2021)
Education is one of the determinants of the quality of Human Resources (HR). The quality of human resources is positively correlated with the quality of education. The quality of education is indicated by good conditions, qualification and fulfillment of all components that must be contained in education. These components are input, process, output, educators and education personnel, facilities and pre-facilities and costs Teacher commitment is part of the affective or emotional reaction of teachers to their experiences at school. Commitment can be seen from being part of the attitude or behavior learned that is related to professional teacher behavior. It is from affective reactions in schools that teachers make decisions (consciously and unconsciously) about the degree of their willingness to personally invernate certain knowledge or learning groups as the teacher's willingness to invest personal resources in teaching tasks. Teacher commitments such as organizational commitments are conceptualized as multidimensional. So the commitment of the teacher is an aspect that must be implemented as a whole based on the call of duty as a profession